2009
DOI: 10.1259/dmfr/88765582
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of high-resolution cone beam computed tomography and charge-coupled device sensors for detecting caries

Abstract: Practising dentists were able to improve their detection of proximal-surface caries extending into the dentin, but not occlusal caries, using 3DX high-resolution cone beam CT images compared with CCD images.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
57
2
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 27 publications
2
57
2
3
Order By: Relevance
“…CBCT offers a number of potential advantages over medical tomography, including easier image acquisition, higher image accuracy, reduced artifacts, lower effective radiation doses, faster scan times, and greater cost-effectiveness [16,17]. Previous research has examined the effectiveness of CBCT in measuring proximal caries depth using dedicated measurement tools [18] as well as the effectiveness of CBCT in detecting occlusal caries [19] and occlusal caries mixed with proximal caries without the use of measurement tools [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…CBCT offers a number of potential advantages over medical tomography, including easier image acquisition, higher image accuracy, reduced artifacts, lower effective radiation doses, faster scan times, and greater cost-effectiveness [16,17]. Previous research has examined the effectiveness of CBCT in measuring proximal caries depth using dedicated measurement tools [18] as well as the effectiveness of CBCT in detecting occlusal caries [19] and occlusal caries mixed with proximal caries without the use of measurement tools [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…The review of recent research showed that some studies have reported greater diagnostic values of CBCT than the other intraoral films for detecting occlusal caries [16,21,25,29]; however, in some studies there were no significant differences [11,28] (the same as in this study). These results vary with the type of CBCT system.…”
Section: Discussionmentioning
confidence: 38%
“…Recent studies about proximal carries detection [13][14][15][16][17][18][19][20][21][22] and occlusal carries detection by CBCT [16,[21][22][23][24][25] are controversial. Most of the articles concluded that CBCT is not better than intraoral films in carries detection.…”
mentioning
confidence: 99%
“…Authors diverge on the superiority of CBCT images against conventional radiographic images for the detection of caries lesions, especially interproximal images. According to Haiter-Neto et al 17 and Young et al 18 , CBCT and digital radiographic images fail to detect incipient enamel caries lesions, as both methods present low sensibility values Charuakkra et al 3 and Valizadeh et al 11 evaluated the CBCT accuracy on proximal caries detection and compared its results to conventional radiographs. Although those studies had similar aims, their conclusions were different.…”
Section: Discussionmentioning
confidence: 99%